2017
DOI: 10.3341/jkos.2017.58.9.1058
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Foveal Microvascular Structures Using Optical Coherence Tomography Angiography in Age-stratified Healthy Koreans

Abstract: Purpose: To evaluate foveal avascular zone (FAZ) microvascular structural changes in healthy Korean subjects stratified by age using optical coherence tomography angiography (OCTA). Methods: Eighty eyes of 43 healthy volunteer subjects who had 20/20 or better best corrected visual acuity without other ocular or systemic disease except vitreous floaters and dry eye syndrome were enrolled and stratified by age group. To measure FAZ size and vascular density (VD) of the superficial capillary plexus (SCP) and deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
1
1
0
1
Order By: Relevance
“…When comparing our results with normal subjects, an increase in SPFAZ was observed across studies [55][56][57][58][59]. DPFAZ shows greater heterogeneity, with some studies showing smaller values [56,58,59], while others reported higher values [55,57]. These results indicate a change in the FAZ area of myopes compared to healthy subjects, which is probably caused by the elongation of the ocular layers.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…When comparing our results with normal subjects, an increase in SPFAZ was observed across studies [55][56][57][58][59]. DPFAZ shows greater heterogeneity, with some studies showing smaller values [56,58,59], while others reported higher values [55,57]. These results indicate a change in the FAZ area of myopes compared to healthy subjects, which is probably caused by the elongation of the ocular layers.…”
Section: Discussionsupporting
confidence: 47%
“…We could not analyze the FAZ in all of the eyes due to segmentation errors, which made measurement difficult. When comparing our results with normal subjects, an increase in SPFAZ was observed across studies [55][56][57][58][59]. DPFAZ shows greater heterogeneity, with some studies showing smaller values [56,58,59], while others reported higher values [55,57].…”
Section: Discussionmentioning
confidence: 45%
“…12 이러한 빛간섭단층혈관조영술 을 이용한 연구를 하기 위해서는 인종, 성별, 나이 등에 따 른 정상 수치에 대한 자료가 필요한데, 국내에서는 정상 성 인을 대상으로 한 연구는 있지만,[13][14][15] 한국 정상 소아를 대 상으로 시행한 표층 및 심부모세혈관총의 혈관밀도와 망막 중심오목무혈관부위 넓이에 관한 연구는 없는 실정이다. 을 받아(승인 번호: DFE21ORIO104) 진행되었다.…”
unclassified